Bright green emission and temperature dependent localized bound exciton transitions from undoped ZnO films. Issue 12 (September 2016) - Meng, Xiangdong; Zhou, Yuxue; Zeng, Xianghua; Chen, Xiaobing
Abstract: Bright green luminescence is achieved from undoped ZnO films prepared by the reaction of oxygen and zinc powder. The green emission band is considered to be mainly due to the singly ionized oxygen vacancies. Temperature dependence of exciton transitions in the undoped ZnO films has been investigated in the range from 10 to 270 K. The PL spectrum at 10 K is dominated by neutral donor-bound exciton (D°X) emissions. The dominant emission centered at about 3.303 eV at above 45 K can be attributed to the localized bound exciton (LBX) transitions related to basal plane stacking faults. LBX transitions can survive up to near room temperature due to the LBX binding energy of 68 meV.